Alloying cast iron with phosphorus to improve the functional properties of products - Proidak , A.Y. (Theory and Practice of Metallurgy, 2024)
Along with the traditional production of cast iron, there are a number of grades with a high phosphorus content. Phosphorous cast iron exhibits a number of beneficial properties. The increased phosphorus content in cast iron leads to an increase in the hydraulic mobility of the solution, improves antifriction properties and wear resistance. In cast iron, which contains more carbon compared to steels, phosphorus forms eutectic that includes Fe3P. Depending on the phosphorus content in lamellar graphite cast iron and high-strength nodular cast iron, the phosphide eutectic appears as misaligned individual inclusions, or a broken or continuous mesh. The paper presents the results of the research on the effect of various phosphorus concentrations on the functional properties of products. In Ukraine’s metallurgical industry, the demand for ferrophosphorus is mainly met by imports, and therefore, supplying metallurgical enterprises with domestic phosphorus-containing materials, such as ferrophosphorus, for smelting a wide range of cast irons appears to be an urgent task.